Persepsi Masyarakat Pesisir Tentang Penerapan Protokol Kesehatan - Veni Nella Syahputri; Endah Anisa Rahma; Giovanni Oktavinanda; Yarmaliza Yarmaliza; Fitriani Fitriani; Teungku Nih Farisni; Nellis Mardhiah (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2021)
Covid-19 has hit the world, including Indonesia and Aceh in particular. This community dedication was carried out on the basis existence of positive cases in Nagan Raya area, Aceh. Meetings and direct banquets attended by many people, as well as community gatherings solely for togetherness to strengthen and build up friendships were still carried out without fully implement health protocol. Additionally, the marine beauty of beaches in Kuala Pesisir sub-district makes this coastal area still crowded even though in a pandemic condition. By considering these facts, the community dedication team held observations related to the perceptions of coastal communities about the implementation of health protocols. The target of this service was 30-50 years old households. The service was executed through observation, data collection and drawing conclusions. The results of the service showed that only 15% of coastal communities target service follow full implementation of health protocol. Therefore, it is highly recommended that coastal communities have the awareness to implement health protocols so that the spread of Covid-19 can be suppressed